Efeitos da exposição pré-natal ao álcool sobre o desenvolvimento e comportamento da prole - Ávila, Mara Aparecida Pereira De (2017)
Prenatal exposure to alcohol is potentially teratogenic. There are many problems caused by consumption of this drug. Some studies suggest that even low quantities of alcohol during the intrauterine life can negatively affect the fetus and / or embryo. In this work, we aim at evaluating the prejudices caused by prenatal exposure to alcohol between 6 and 19 days of gestation, by treatment with liquid diet containing 25% ethanol-derived calories. The controls consisted of pair-fed dams (receiving an isocaloric liquid diet containing 0% ethanol-derived calories) and dams with ad libitum access to control diet. The obtained results showed that pregnant rats and female mice submitted to the treatment with alcohol during the pregnancy presented reduction of the daily diet consumption, when compared to the animals (control) with alcohol-free diet. This reflected in lower weight gain, considering pregnant rats in the alcohol diet group and pair feeding. The alcohol dosage lets the detection of low levels of ethanol in the animals’ blood. Consumption of these concentrations did not cause changes in the number of pups born per mother. However, alcohol group animals presented high death level after birth, low weight after born and reduction of the weight and nasoanal length which stays until the beginning of the adulthood, failures in the physical and reflexive development considering the parameters of eyes opening and negative geotaxis in females and the parameter of righting up in males. The behavioral evaluation of the males during the adolescence has also revealed prejudices as reduction of the interactions in isolated animals of alcohol group and reduction of neuronal activation in regions of the prefrontal cortex (agranular insular, pre-limbic, cingulate and piriform) and accumbens shell in play behavior test. In addition to these changes, the behavioral evaluation during adult life indicated that the male and female offspring of rats exposed to alcohol presented a reduction in the preference for the sexual incentive during the sexual motivation test. Also the evaluation of the adulthood pointed out predictive response of depression, evidenced by the tail suspension test and increased neuronal activation in central areas related to stress (Locus coerulos and paraventricular nucleus of the hypothalamus). It is important to note that we do not find alterations in the maternal behavior during the lactation. The results presented here in shows evidence that, low concentrations of alcohol are teratogenic for the offspring, generating physical and behavior problems and emphasizing the importance of abstinence from alcohol consumption during gestation.